2021
DOI: 10.1037/ppm0000275
|View full text |Cite
|
Sign up to set email alerts
|

A new avenue to reach out for the stars: The association of celebrity worship with problematic and nonproblematic social media use.

Abstract: Social media has opened an avenue for reciprocal interactions between celebrities and their fans, encouraging individuals with a tendency to become obsessed with celebrities to extend their online social network with celebrity friends. Celebrity worship has been associated with weak social skills and addictive behaviors (e.g., problematic Internet use, compulsive buying) in previous studies. This study investigated how interpersonal skills and addictive tendencies may affect the social media use of individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…An early study by Martin et al [ 2 ] proposed that celebrity worship may interfere with the information processing of individuals who are more prone to get absorbed in the personal details of a celebrity. Celebrity worship, as an excessive behavior, was also associated with several behavioral addictions (e.g., problematic Internet and social media use [ 7 , 8 ], compulsive buying [ 9 ], gambling addiction [ 10 ]), and these problematic behaviors are known to have negative effects on school/work performance, social relationships and cognitive functioning [ 11 ]. Therefore, it can be expected that excessive involvement with an admired celebrity may interfere with cognitive performance due to the limited ability to focus on other things than the celebrity.…”
Section: Introductionmentioning
confidence: 99%
“…An early study by Martin et al [ 2 ] proposed that celebrity worship may interfere with the information processing of individuals who are more prone to get absorbed in the personal details of a celebrity. Celebrity worship, as an excessive behavior, was also associated with several behavioral addictions (e.g., problematic Internet and social media use [ 7 , 8 ], compulsive buying [ 9 ], gambling addiction [ 10 ]), and these problematic behaviors are known to have negative effects on school/work performance, social relationships and cognitive functioning [ 11 ]. Therefore, it can be expected that excessive involvement with an admired celebrity may interfere with cognitive performance due to the limited ability to focus on other things than the celebrity.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from impulsive buying intent, previous studies have also indicated that celebrity worship differs between men and women. Zsila et al (2020) measured celebrity worship using the CAS and found the levels to be higher among women than men. Furthermore, men and women have been shown to have different patterns of celebrity worship behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside research about the influence of audience and media content's characteristics on PSR, previous literature also focused on the theoretical association between media use and PSR (Giles, 2002;Klimmt et al, 2006). Recent research has underlined that PSR are positively associated with social media use and more specifically with social media addiction (Baek et al, 2013;de Bérail et al, 2019;Lim et al, 2020;Zsila et al, 2021).…”
Section: Social Media Addictionmentioning
confidence: 99%